Impacts of Electric Vehicle Penetration on the Frequency Stability of Curaçao’s Power Network - Daniela Vásquez-Cardona; Sergio D. Saldarriaga-Zuluaga; Santiago Bustamante-Mesa; Jesús M. López-Lezama; Nicolás Muñoz-Galeano (World Electric Vehicle Journal)
Assessing the impact of electric vehicle (EV) integration on power systems is crucial, particularly regarding frequency stability, which often remains largely unaddressed, especially in developing countries. This paper examines the effects of EV penetration on the frequency stability of Curaçao’s power network, an aspect not previously studied for the island. As a key contribution, we present a representative model of Curaçao’s power network, adjusting the dynamic models of the speed governors of synchronous machines, using data available to the academic community. Additionally, we analyze the impacts of EVs on the grid’s frequency stability under different EV participation scenarios. To achieve this, simulations were conducted considering various EV participation scenarios and different types of chargers to assess their impact on grid stability. The study evaluates key frequency stability metrics, including the rate of change of frequency (RoCoF) as well as the highest and lowest frequency values during the transient period. The results indicated that higher EV penetration can significantly impact frequency stability. The observed increase in the RoCoF and frequency zenith values suggests a weakening of the grid’s ability to withstand frequency disturbances, particularly in high-EV-penetration scenarios.